Oral Disposition Index in Obese Youth from Normal to Prediabetes to Diabetes: Relationship to Clamp Disposition Index - Sjaarda, Lindsey George (2012)
OBJECTIVE: To assess the glucose disposition index (DI) using an oral glucose tolerance test (OGTT; oDI) compared with the DI measured from the combination of the euglycemic-hyperinsulinemic and hyperglycemic clamps (cDI) in obese pediatric subjects spanning the range of glucose tolerance. STUDY DESIGN: Overweight/obese adolescents (n=185) with varying glucose tolerance (87 normal [NGT], 54 impaired [IGT], 31 with type 2 diabetes [T2DM] and 13 with type 1 diabetes [OT1DM]) completed an OGTT and both a hyperinsulinemic-euglycemic and a hyperglycemic clamp study. Indices of insulin sensitivity and β-cell function were calculated, and four different oDI estimates were calculated as the products of insulin and C-peptide-based sensitivity and secretion indices. RESULTS: Mirroring the differences across groups by cDI, the oDI estimates were greatest in NGT and lowest in T2DM and OT1DM. The insulin-based oDI estimates correlated with cDI overall (r≥0.74, P<0.001) and within each glucose tolerance group (r≥0.40, P<0.001). Also, oDI and cDI predicted 2-h OGTT glucose similarly. CONCLUSIONS: Oral disposition index is a simple surrogate estimate of β-cell function relative to insulin sensitivity that can be applied to obese adolescents with varying glucose tolerance in large-scale studies where the applicability of clamp studies is limited due to feasibility, cost and labor intensiveness.